2017
DOI: 10.1159/000479412
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a/b Inhibit Tumor Growth and Angiogenesis by Targeting the HGF-VEGF Axis in Gastric Carcinoma

Abstract: Background/Aims: Abnormal expression of HGF is found in various cancers and correlates with tumor proliferation, metastasis and angiogenesis. However, the regulatory mechanism of the HGF-VEGF axis remains unclear. Methods: The expression characteristic of HGF in human gastric cancer tissues was shown by an immunohistochemistry assay, and the expression levels of target protein were detected by Western blot. The relative levels of miR-26a/b and target mRNA were examined by qRT-PCR. We used bioinformatics tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In this study, we observed that both USCs-EVs and iMSCs-EVs promoted C2C12 myoblast proliferation. Previous studies reported that VEGF, HGF and IGF-1 were not only potential proangiogenic factors but also promoted myoblast proliferation [53][54][55][56][57][58][59]. In the present study, we found that VEGF, HGF and IGF-1 were loaded in the USCs-EVs.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we observed that both USCs-EVs and iMSCs-EVs promoted C2C12 myoblast proliferation. Previous studies reported that VEGF, HGF and IGF-1 were not only potential proangiogenic factors but also promoted myoblast proliferation [53][54][55][56][57][58][59]. In the present study, we found that VEGF, HGF and IGF-1 were loaded in the USCs-EVs.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies showed that miRNAs play vital roles in GC carcinogenesis [32][33][34]. In addition, miR-19b regulates hTERT mRNA expression by targeting PITX1 mRNA in melanoma cells [26], and enhanced miR-886-3p expression regulates cell migration, proliferation, and apoptosis by targeting PITX1 in clear cell renal cell carcinoma [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Mechanically, miR‐26a represses VEGF signalling via directly targeting NgBR, and therefore inhibit angiogenesis by performing proliferation, migration and tube formation in HUVECs 118. Furthermore, miR‐26a/b is decreased in gastric cancer and HCC,119, 120 which can inhibit angiogenesis in gastric cancer and reduce the proliferation and migration of gastric cancer via targeting the HGF‐VEGF axis 119. In addition, miR‐26b‐5p is obviously down‐regulated in HCC tissues and HCC cell lines, which represses the apoptosis and tube formation of HCC cells and inhibits angiogenesis via decreasing the expression of VE‐cadherin, Snail and MMP‐2 in vitro and in vivo 120.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%